PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI PELAKU KEJAHATAN - Mulyati, Dewi; Dahwir, Ali (Solusi, 2022)
The focus of this research is to understand how the form of legal protection provided by the state to children who commit crimes. The type of research used is library research. Based on the results of the study, it is known that the form of protection for children who commit crimes is given at every stage of the juvenile criminal justice process. Starting from the arrest stage, detention stage, investigation stage, prosecution, and trial stage, as well as during the coaching period. Another form of protection is efforts to settle criminal cases outside the trial, namely children's cases are always pursued through diversion and this is required to be done at every stage of the juvenile criminal justice process. The purpose of providing legal protection to child offenders is also the implementation of respect for the perpetrators' human rights so that they are not psychologically disturbed, have legal certainty, and to avoid arbitrary and unfair treatment.